2018
DOI: 10.3390/ijerph15102211
|View full text |Cite
|
Sign up to set email alerts
|

A Metagenomic Approach to Evaluating Surface Water Quality in Haiti

Abstract: The cholera epidemic that occurred in Haiti post-earthquake in 2010 has resulted in over 9000 deaths during the past eight years. Currently, morbidity and mortality rates for cholera have declined, but cholera cases still occur on a daily basis. One continuing issue is an inability to accurately predict and identify when cholera outbreaks might occur. To explore this surveillance gap, a metagenomic approach employing environmental samples was taken. In this study, surface water samples were collected at two ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 53 publications
(56 reference statements)
0
20
0
Order By: Relevance
“…Metagenomic samples were sequenced with an average of 1.5 x 10 7 (min = 4.8 x 10 6 ; max = 3.0 x 10 7 ) sequence read depth across samples ( Table 2). The low DNA input observed in BW samples B and C resulted in a slightly lower number of reads, 4.8 x 10 6 and 5.6 x 10 6 , respectively, compared to the number of reads observed in samples A, D, E, and F and that employed in similar metagenomic investigations employing Ion Torrent chemistry [26].…”
Section: Plos Onementioning
confidence: 69%
See 3 more Smart Citations
“…Metagenomic samples were sequenced with an average of 1.5 x 10 7 (min = 4.8 x 10 6 ; max = 3.0 x 10 7 ) sequence read depth across samples ( Table 2). The low DNA input observed in BW samples B and C resulted in a slightly lower number of reads, 4.8 x 10 6 and 5.6 x 10 6 , respectively, compared to the number of reads observed in samples A, D, E, and F and that employed in similar metagenomic investigations employing Ion Torrent chemistry [26].…”
Section: Plos Onementioning
confidence: 69%
“…Base-calling error probabilities (P) were evaluated using Phred Quality Score (Q), defined by: Q = −10log 10 (P). Residual primer and adapter content were trimmed using the Joint Genome Institute Bestus Bioinformatics Decontamination Using Kmers (BBDuk) tool (v.38.07) [36] with a previously defined read quality trimming threshold [26]. Reads were trimmed from both ends until the mean quality value across each base position in the reads for all sample read libraries were above a Phred Quality Score of 17 for at least 80% of the read lengths, i.e., probability of correct base call was at least 98%.…”
Section: Metagenomic Sequencing Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, Roy et al . () showed that shotgun metagenomics (sequencing all of the DNA in a sample) could be used to monitor surface waters for Vibrio cholerae ; however, this was done in a region with a recent cholera epidemic, and the target might be assumed to be present at a high concentration. In contrast use of this method for surveillance of enteric pathogens, which might be present in very small number, is problematic.…”
Section: Metagenomicsmentioning
confidence: 99%